Model Oriented Approach to Code Generation for Normative Multi-Agent Systems - R. Júnior, Robert M.; Freire, Emmanuel S. S.; Cortés, Mariela I. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
The increasing complexity of the normative multi-agent systems (MAS) development represents a challenge to software engineering. Model driven approach promotes a fast and consistent software development through the use of software models. In order to reduce the semantic gap that exists between modeling and implementation levels and surround the natural complexity associated to Normative MAS development, this work proposes the use of a model driven approach to develop Normative MAS. A template-based approach was used to automate the code generation process from NorMAS-ML models to the specific platform (JADE), it was named JAMDER 2.0 that contains all resources of JADE and adds new entities to adapt the concepts of each other.